Electrical Conduction System Remodeling in Streptozotocin-Induced Diabetes Mellitus Rat Heart - Zhang, Yu; Wang, Yanwen; Yanni, Joseph; Qureshi, Mohammed Anwar; Logantha, Sunil Jit R. J.; Kassab, Sarah; Boyett, Mark R.; Gardiner, Natalie J.; Sun, Hong; Howarth, Frank Christopher; Dobrzynski, Halina (Frontiers in Physiology, 2019)
Cardiovascular complications are common in type 1 diabetes mellitus (TIDM) and there is an increased risk of arrhythmias as a result of dysfunction of the cardiac conduction system (CCS). We have previously shown that, in vivo, there is a decrease in the heart rate and prolongation of the QRS complex in streptozotocin-induced diabetic rats indicating dysfunction of the CCS. The aim of this study was to investigate the function of the ex vivo CCS and key proteins that are involved in pacemaker mechanisms in TIDM. RR interval, PR interval and QRS complex duration were significantly increased in diabetic rats. The beating rate of the isolated sinoatrial node preparation was significantly decreased in diabetic rats. The funny current density and cell capacitance were significantly decreased in diabetic nodal cells. Western blot showed that proteins involved in the function of the CCS were significantly decreased in diabetic rats, namely: HCN4, Cav1.3, Cav3.1, Cx45, SERCA2a and NCX1 in the sinoatrial node; RyR2, SERCA2a and NCX1 in the atrioventricular junction and Cx40, Cx43, Cx45, RyR2, SERCA2a in the Purkinje network. We conclude that there are complex functional and cellular changes in the CCS in TIDM. The changes in the proteins involved in the function of this electrical system are expected to adversely affect the action potential generation and propagation, and thus arrhythmiogenesis.